2022
DOI: 10.1007/s11060-022-04176-4
|View full text |Cite
|
Sign up to set email alerts
|

Resection extent and BRAF V600E mutation status determine postoperative tumor growth velocity in pediatric low-grade glioma: results from a single-center cohort analysis

Abstract: Purpose Despite excellent long-term overall survival rates, pediatric low-grade gliomas (pLGG) show high variety of clinical behavior regarding progress or senescence post incomplete resection (IR). This study retrospectively analyzes tumor growth velocity (TGV) of pLGG before surgery and after IR to investigate the impact of surgical extent, tumor location and molecular BRAF status on postoperative residual tumor growth behavior. Methods Of a total of 172… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In line with this, of all patient‐ and procedure‐related factors that predicted the development of postoperative complications, preoperative tumor volume >80 cm 3 and complete resection correlated strongly with an increased number of neurosurgical morbidity. On the other hand, if radical resections are to be avoided, available evidence indicates that the percentage of residual tumor is less important for long‐term prognosis 14,18,45 . Thus, (re‐)resections have to be restricted with regard to the complication/impairments and the limited options for re‐intervention in the SML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this, of all patient‐ and procedure‐related factors that predicted the development of postoperative complications, preoperative tumor volume >80 cm 3 and complete resection correlated strongly with an increased number of neurosurgical morbidity. On the other hand, if radical resections are to be avoided, available evidence indicates that the percentage of residual tumor is less important for long‐term prognosis 14,18,45 . Thus, (re‐)resections have to be restricted with regard to the complication/impairments and the limited options for re‐intervention in the SML.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if radical resections are to be avoided, available evidence indicates that the percentage of residual tumor is less important for long-term prognosis. 14,18,45 Thus, (re-) resections have to be restricted with regard to the complication/ impairments and the limited options for re-intervention in the SML.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…67 In 2022, Gorodezki et al analyzed the tumor growth velocity of pediatric LGGs to evaluate the impact of BRAF V600E mutation and KIAA1549:BRAF fusion on tumor progression following subtotal resection. 80 The authors found that BRAF V600E mutant pediatric LGGs showed higher regrowth rates compared with BRAF wildtype pediatric LGGs. 80 The authors also reported that there was no significant difference in regrowth rates between pediatric LGGs that harbored KIAA1549:BRAF fusion and those that did not.…”
Section: The Impact Of Other Genomic Alterations Coexistence On Braf ...mentioning
confidence: 96%
“…80 The authors found that BRAF V600E mutant pediatric LGGs showed higher regrowth rates compared with BRAF wildtype pediatric LGGs. 80 The authors also reported that there was no significant difference in regrowth rates between pediatric LGGs that harbored KIAA1549:BRAF fusion and those that did not. 80…”
Section: The Impact Of Other Genomic Alterations Coexistence On Braf ...mentioning
confidence: 96%